Chalcedon in context church councils 400-700 - Price, Richard, 1947-; Whitby, Mary, 1951- (Translated texts for historians. Contexts ;, 2009)
This collection of essays has its origin in a conference held at Oxford in 2006 to mark the publication of the first English edition of the Acts of Chalcedon. Its aim is to place Chalcedon in a broader context, and bring out the importance of the acts of the early general councils from the fifth to the seventh century, documents that because of their bulk and relative inaccessibility have received only limited attention till recently. This volume is evidence that this situation is now rapidly changing, as historians of late antiquity as well as specialists in the history of the Christian Church discover the richness of this material for the exploration of common concerns and tensions across the provinces of the Later Roman Empire, language use, networks of influence and cultural exchange, and political manipulation at many different levels of society.